2021
DOI: 10.3390/ijerph18094834
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effectiveness of Performing Advanced Resuscitation Procedures Undertaken by Two- and Three- Person Basic Medical Rescue Teams in Adults under Simulated Conditions

Abstract: (1) Objective: Paramedics as a profession are a pillar of the State Medical Rescue system. The basic difference between a specialist and a basic team is the composition of members. The aim of the study was to benchmark the effectiveness of performing advanced resuscitation procedures undertaken by two- and three-person basic emergency medical teams in adults under simulated conditions. (2) Design: The research was observational. 200 two- and three-people basic emergency medical teams were analyzed during advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
(57 reference statements)
0
5
0
Order By: Relevance
“… 14 Several simulation studies demonstrated superior CPR quality (chest compression quality and fraction) in teams larger than two, along with a more efficient achievement of critical CPR endpoints such as rhythm recognition, adrenaline administration, and tracheal intubation. 20 , 21 , 22 No significant difference in the no-flow fraction was observed between teams of two, three, and four paramedic students in one simulated ALS/CPR study. 23 One study comparing team compositions found that teams of two paramedics were more prone to errors and generally slower in most interventions (except for tracheal intubation), compared to paramedic-emergency medical technician (EMT) teams.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“… 14 Several simulation studies demonstrated superior CPR quality (chest compression quality and fraction) in teams larger than two, along with a more efficient achievement of critical CPR endpoints such as rhythm recognition, adrenaline administration, and tracheal intubation. 20 , 21 , 22 No significant difference in the no-flow fraction was observed between teams of two, three, and four paramedic students in one simulated ALS/CPR study. 23 One study comparing team compositions found that teams of two paramedics were more prone to errors and generally slower in most interventions (except for tracheal intubation), compared to paramedic-emergency medical technician (EMT) teams.…”
Section: Resultsmentioning
confidence: 85%
“… Klosiewicsz (2020A) 7 Paramedics ( n = 104) Mechanical CC during ALS/CPR CC quality Use of mechanical CC device increased CC quality measures Klosiewicsz (2020B) 8 Paramedics ( n = 104) Mechanical CC during ALS/CPR Intervals between rhythm checks, duration of rhythm check, time to medication Use of mechanical CC device: improved adherence to ALS protocol and earlier achievement of resuscitation endpoints. Krzyzanowski (2021) 21 Paramedics ( n = 463) Team size comparison Time to critical interventions, CC quality measures, medication errors Three-member teams: faster times to critical interventions, higher CC quality, less medication errors. Martin-Gill (2010) 23 Paramedic students ( n = 40) Team size comparison No-flow fraction No significant difference in no-flow fraction between 2-, 3- and 3-member teams.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations